Adhesion Molecules: Function and Inhibition - Ley, Klaus (Progress in Inflammation Research, 2007)
Inflammatory cell recruitment requires the concerted action of at least five major sets of adhesion molecules: integrins, immunoglobulin-like molecules, selectins, carbohydrate structures serving as selectin ligands, and certain ectoenzymes. This volume gives a comprehensive overview on the most relevant leukocyte and endothelial adhesion molecules. The chapters are written by leaders in the field and focus on the biology, structure, function, and regulation of adhesion molecules. Currently approved adhesion molecule-based therapies are reviewed and an outlook for future approaches is also provided. The book is of interest to clinicians and scientists from immunology, physiology, cancer research, rheumatology, allergology, infectious diseases, gastroenterology, pulmonology and cardiology.